Rhodium‐Catalyzed Synthesis of 2, 5‐Epoxybenzo[f][1, 4]oxazepines by Tandem Reaction of 1‐Sulfonyl‐1, 2, 3‐triazoles and Salicylaldehydes. Issue 29 (11th September 2015) - Shi, Yinping; Yu, Xing; Li, Chuan‐Ying
Abstract: Readily available 1‐sulfonyl‐1, 2, 3‐triazoles were converted into α‐imino carbenes in the presence of catalytic amounts of rhodium(II) salts. The carbenes underwent a tandem reaction with salicylaldehydes to provide a series of functionalized 2, 5‐epoxybenzo[ f ][1, 4]oxazepines in high yields. Abstract : A novel protocol for the synthesis of 2, 5‐epoxybenzo[ f ][1, 4]oxazepines is developed. The complicated ring system can be constructed from readily available N ‐sulfonyl‐1, 2, 3‐triazoles and salicylaldehyde derivatives in a one‐pot procedure. Many valuable functional groups are well tolerated in this transformation. [Rh2 (piv)4 ] = dirhodium(II) tetrapivalate.